Job Crafting Towards Self （Strengths and Interests） and Others（Contribution and Collaboration）: An Integrative Model Based on the Four Pathways of Work Meaningfulness Proposed by Rosso et al. (2010) - Rie FUJISAWA (AAOS Transactions)
In the face of contemporary societal uncertainties, the significance of careers and work is far from self-evident. Individuals need to craft jobs and careers with personal meaning. Wrzesniewski and Dutton （2001） introduced the concept of job crafting, offering a lens through which employees can modify their work tasks and relationships to construct meaningful work experiences. However, there needs to be more empirical research on job crafting to understand how individuals create and transform meaningful experiences in the workplace. This paper undertakes a selective review of studies that expand upon Wrzesniewski and Dutton’s （2001） seminal model, identifying three distinct directions of extension research. An integrated model is proposed, encapsulating all three directions and aligning with Rosso et al.’s （2010） four-pathway framework of work meaningfulness.